2013
DOI: 10.1021/cb4001926
|View full text |Cite
|
Sign up to set email alerts
|

Protein Recognition by Short Peptide Reversible Inhibitors of the Chromatin-Modifying LSD1/CoREST Lysine Demethylase

Abstract: The combinatorial assembly of protein complexes is at the heart of chromatin biology. Lysine demethylase LSD1(KDM1A)/CoREST beautifully exemplifies this concept. The active site of the enzyme tightly associates to the N-terminal domain of transcription factors of the SNAIL1 family, which therefore can competitively inhibit the binding of the N-terminal tail of the histone substrate. Our enzymatic, crystallographic, spectroscopic, and computational studies reveal that LSD1/CoREST can bind to a hexapeptide deriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
70
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 64 publications
(74 citation statements)
references
References 24 publications
0
70
0
3
Order By: Relevance
“…This peptide was investigated in the framework of a study aimed at identifying the sequence features that confer specificity to the interaction between the LSD1/CoREST active site and the N-terminal SNAG domain of SNAIL1 and related transcription factors [16], [49]. Interestingly, the crystallographic analysis revealed that this peptide binds not only to the catalytic site but also in a distinct shallow cleft in the AOD domain (Figure 6).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This peptide was investigated in the framework of a study aimed at identifying the sequence features that confer specificity to the interaction between the LSD1/CoREST active site and the N-terminal SNAG domain of SNAIL1 and related transcription factors [16], [49]. Interestingly, the crystallographic analysis revealed that this peptide binds not only to the catalytic site but also in a distinct shallow cleft in the AOD domain (Figure 6).…”
Section: Resultsmentioning
confidence: 99%
“…The crystallographic data and three-dimensional structure of LSD1/CoREST bound to the peptide Pro-Leu-Ser-Phe-Leu-Val were described before [16] (PDB ID: 3ZMV). Briefly, the peptide complex was obtained by crystal soaking in solutions consisting of 1.6 M sodium/potassium tartrate, 100 mM N-(2-acetamido)-2-iminodiacetic acid pH 6.5, 10% (v/v) glycerol, and 2–5 mM peptide for 3 h. X-ray diffraction data were collected at 100 K at the Swiss Light Source (Villigen, Switzerland).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, (bis)amidines such as CBB1007 [51] have been reported as reversible LSD1 inhibitors to selectively target cancer stem cells derepressing epigenetically suppressed genes in vivo. Also peptides were described as LSD1 inhibitors, such as the pLys4Met peptide [52], some synthetic cyclic peptides [53], and a series of short peptides based on the SNAIL sequence exhibiting antiproliferative activities [54]. Among reversible LSD1 inhibitors, amidoximes 7 [55], dithiocarbamates 8 [56], substituted triazoles 9 [57], and benzohydrazides 10 [58] have been recently reported.…”
Section: Introductionmentioning
confidence: 99%
“…The LSD1 inhibitory activity of pargyline has been tested in prostate cancer cells [7]. Finally, a fourth class of LSD1 inhibitors mimics the peptide structure of LSD1 substrates, such as histone H3 tails [35,36]. For example, CBB1007 is an amidino-guanidinium compound that was developed based on the crystal structure of LSD1 associated with a peptide inhibitor derived from the N-terminal tail of H3 [36].…”
Section: Introductionmentioning
confidence: 99%